Actual work programme. Range Science Unit, 1985 - Ridder, N.A. de; Wagenaar, K.T. (International Livestock Centre for Africa, 1984)
Outlines the 1985 actual workprogramme of the Range Science Unit (ILCA) which includes literature research, remote sensing and modelling. Lists also some minor activities planned and budget proposal.